مراسيم زيارة قبر الإمام الحسين في مرويات الإمام الصادق عليهما السلام من خلال كتاب كامل الزيارات لابن قولويه -الاغتسال انموذجاً- - إيمان حسن مجيسر ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
One of the greatest blessings that Gad has bestowed upon is the sending of the prophets , messengers and imams to all the creatures , to show the slaves the truth of slavery and unification, and to invite him to God alone and to realize the truth and fight the deviation from the Islamic religion in all its froms. Who have performed their missionary duties , thus making his tomb ashrine to all the advocates of reform and liberation .I have promised to visit him from the platforms of allegiance and adhere to his approach .